Subsegmental resection preserves regional pulmonary function: A focus on thoracoscopy. Issue 7 (14th February 2021) - Kuroda, Hiroaki; Sakata, Shozo; Takahashi, Yusuke; Nakada, Takeo; Oya, Yuko; Sugita, Yusuke; Sakakura, Noriaki; Matushita, Hiroakazu; Sakao, Yukinori
Abstract: Background: The aim of this study was to evaluate regional postoperative preserved pulmonary function (PPPF) and three‐dimensional (3D) volumetric changes according to the number of resected subsegments and investigate the factors that most affected pre‐/post PPPF. Methods: Patients who underwent thoracoscopic lobectomy ( n = 73), and segmentectomy ( n = 87) were eligible for inclusion in the study. They were classified according to the number of resected subsegments which ranged from 1 to 10. The percentage of pre‐/postoperative forced expiratory volume in 1 s (FEV1) was used for comparison. Furthermore, lung volumetric changes were calculated using 3D computed tomography (CT) volumetry. Results: The percentage of pre‐/postoperative EFV1 between 4 and 5–7 and between 5–7 and 10 were significant ( p = 0.03 and p < 0.01, respectively), but not between 1–2 to 4 ( p = 0.99). The difference between volumetric changes in the left lower lobe of patients with a number of resected subsegments was significant ( p < 0.01). On univariate and multivariate analyses, chronic inflammation was significant for decrease in recovery percentages. When the PPPF was compared among resected subsegments, it gradually decreased with an increase in the number of patients without a postoperative procrastination of inflammation ( p < 0.01). Conclusions: Segmentectomy is feasible and useful for PPPF. Even a relatively large‐volume resection procedure where 5–7 subsegments are resected can preserve pulmonary function. Chronic inflammation was statistically identified as a risk factor for postoperative preserved pulmonary function. Key points: Abstract : Segmentectomy is feasible and useful for postoperative preserved pulmonary function. However, chronic inflammation has been statistically identified as a risk factor for postoperative preserved pulmonary function.